Heat stabilization of blood spot samples for determination of metabolically unstable drug compounds. (January 2013) - Blessborn, Daniel; Sköld, Karl; Zeeberg, David; Kaewkhao, Karnrawee; Sköld, Olof; Ahnoff, Martin
Background: Sample stability is critical for accurate analysis of drug compounds in biosamples. The use of additives to eradicate the enzymatic activity causing loss of these analytes has its limitations.Results: A novel technique for sample stabilization by rapid, high-temperature heating was used. The stability of six commercial drugs in blood and blood spots was investigated under various conditions with or without heat stabilization at 95°C. Oseltamivir, cefotaxime and ribavirin were successfully stabilized by heating whereas significant losses were seen in unheated samples. Amodiaquine was stable with and without heating. Artemether and dihydroartemisinin were found to be very heat sensitive and began to decompose even at 60°C.Conclusion: Heat stabilization is a viable technique to maintain analytes in blood spot samples, without the use of chemical additives, by stopping the enzymatic activity that causes sample degradation.